Is Japan the champion of the colored races? The negro's stake in democracy. [With contribs. of T. Bassett, A.W. Berry, C. Briggs a.o.] (Workers Library Publishers, 1938)
Ed. by the Negro Commission National Committee C.P. U.S.A.